In vitro sensitivity to methyl-prednisolone is associated with clinical response in pediatric idiopathic nephrotic syndrome. - Cuzzoni, E; De Iudicibus, S; Stocco, G; Favretto, D; Pelin, M; Messina, G; Ghio, L; Monti, E; Pasini, A; Montini, G; Decorti, G (Clin Pharmacol Ther, 2016)
The aim of this study was to evaluate the in vitro steroid sensitivity as a predictor of clinical response to glucocorticoids in childhood idiopathic nephrotic syndrome (INS). Seventy-four patients (median age 4.33, interquartile range [IQR] 2.82-7.23; 63.5% male) were enrolled in a prospective multicenter study: in vitro steroid inhibition of patients' peripheral blood mononuclear cell proliferation was evaluated by [methyl-(3) H] thymidine incorporation assay at disease onset (T0) and after 4 weeks (T4) of treatment. Steroid dependence was associated with increased in vitro sensitivity at T4 assessed both as drug concentration inducing 50% of inhibition (IC50 ; odds ratio [OR] = 0.48, 95% confidence interval [CI] = 0.24-0.85; P = 0.0094) and maximum inhibition at the highest drug concentration (Imax ; OR = 1.13, 95% CI = 1.02-1.31; P = 0.017). IC50 > 4.4 nM and Imax < 92% at T4 were good predictors for optimal clinical response. These results suggest that this test may be useful for predicting the response to glucocorticoid therapy in pediatric INS.